1984
DOI: 10.4319/lo.1984.29.5.1037
|View full text |Cite
|
Sign up to set email alerts
|

Carbon flow through oxygen and sulfate reduction pathways in salt marsh sediments1

Abstract: We measured surface 0, uptake, 35S0.,2-reduction, and total sediment metabolism (CO, production) in sediments (O-30 cm) supporting stands of short Spartina alterniflora in a New England salt marsh. Sediment CO, production was highest at the surface where 0, was present and declined rapidly with depth. In deeper sediments (below 5 cm) CO, production was equal to 35S0,2-reduction as determined by the Cr2+ reduction technique. Time-course experiments using CO, production and 35S04?-reduction (by Cr2+ reduction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(69 citation statements)
references
References 36 publications
3
65
1
Order By: Relevance
“…Thus, a sulfate reduction equivalent to about 5 0 % of the oxygen uptake was also found in other organic-rich sediments and marshes (Jsrgensen 1982, Howes et al 1984, Howarth 1984. Because of extensive reoxidation of produced sulfide by oxygen in such sediments, close to half of the measured oxygen uptake may be diverted to this process (Jsrgensen 1977).…”
Section: Uptake and S@-reductionmentioning
confidence: 91%
“…Thus, a sulfate reduction equivalent to about 5 0 % of the oxygen uptake was also found in other organic-rich sediments and marshes (Jsrgensen 1982, Howes et al 1984, Howarth 1984. Because of extensive reoxidation of produced sulfide by oxygen in such sediments, close to half of the measured oxygen uptake may be diverted to this process (Jsrgensen 1977).…”
Section: Uptake and S@-reductionmentioning
confidence: 91%
“…As an alternative to harvest methods, fluxes of CO2 and CH, have been used to estimate gross and net macrophyte productivity under ambient field conditions (Blum et al 1978, Giurgevich & Dunn 1978, Howes et al 1984 or under experimental conditions such as elevated atmospheric CO2 concentrations (Drake 1984, Curtis et al 1989, Azc6n-Bieto et al 1994 or manipulated soil salinities (Pezeshki 1991, Hwang & Morris 1994. The carbon gas flux technique integrates processes that occur within and between aboveground and belowground compartments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The observed depth trends in the upper O-l 5 cm have also been recognized in other coastal sediments, notably in salt marshes of the cast coast of the United States (Howes et al 1984;King et al 1985;King 1988). The most extreme example was reported by King ( 1988) for a Georgia salt-marsh soil where the distribution of reduced 35S in AVS, So, and FeS, changed from 1.7, 95.3, and 4.6% at the surface to 35.1, 19.2, and 52.4% at lo-cm depth.…”
Section: Discussionmentioning
confidence: 68%
“…Howarth and coworkers concluded that pyrite is a much more dynamic pool than previously expected. Later studies have confirmed that the formation ofradiolabeled pyrite plays a significant role in salt marshes and coastal sediments (Howes et al 1984;King 1988). Elemental sulfur, So, was also found to accumulate much of the reduced label from 35S042-reduction (Howarth and Jerrgcnsen 1984;King et al 1985;King 1988).…”
Section: Acknowledgmentsmentioning
confidence: 83%